Clonorchis sinensis calcium-binding protein Cs16 causes acute hepatic injury possibly by reprogramming the metabolic pathway of bone marrow-derived monocytes - Li, Qi; Li, Xiao; Kan, Shuo; Zhu, Ting-Jun; Li, Chang; Du, Xin-Yue; Wang, Xin; Yan, Hui-Bo; Wu, Chen-Yun; Chen, Guang-Jie; Qian, Men-Bao; Yan, Min; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Clonorchis sinensis infection results in various complications in the liver and biliary systems and is a neglected tropical disease in Eastern Asia. In this study, we report that C. sinensis calcium-binding protein Cs16 activates host immune cells and induces immunopathology in liver. Methods Immunohistochemistry was used to detect the localization of Cs16 in C. sinensis adult worms. ELISA was used to detect the serum levels of anti-Cs16 IgG antibody in infected humans and mice. Bile duct injection model was used to figure out the role of Cs16 in vivo. RT-qPCR and ELISA were used to detect the cytokine production from Cs16-treated BMMs in vitro. Seahorse assay was used to detect the metabolic pathway of Cs16-treated BMMs in vitro. Result Cs16 localizes in the tegument and gut of C. sinensis. Humans and mice with C. sinensis infection exhibited increased levels of anti-Cs16-specific antibody. Using the bile duct injection technique, we found that Cs16 induced obvious inflammation and hepatic necrosis in vivo. Cs16 treatment caused the upregulation of inflammatory cytokines in innate immune cells. Moreover, Cs16-treated monocytes relied more on the glycolytic metabolic pathway. Discussion Our findings suggest that Cs16 is a potential pathogenic factor derived from C. sinensis adult worm. By reprogramming the metabolic pathway of innate immune cells, Cs16 triggers pro-inflammatory responses in the liver, and therefore, Cs16 is a potential target for the prevention and treatment of clonorchiasis.